Growth charts for children aged 6-17 years in Shanxi, China: comparison with other cities of China and WHO - Guoqiang Hou; Kunkun Li; Wenjun Cao; Mengmeng Tao; Wei Tian; Ruimin Chang (BMC, 2024)
Abstract Background Growth charts are an important method for evaluating a child's health, growth, and nutritional status. It is essential to monitor the growth of children and adolescents using growth charts. Objectives To present body mass index (BMI)-for-age references reflecting children's growth in Shanxi. We also compare our new data with growth references of other cities of China and World Health Organization (WHO) growth standards. Methods A stratified cluster random sampling method was used to recruit 5461 children and adolescents aged 6-17 years. Height and weight were measured and BMI was calculated. The LMS method was used to calculate the percentile values of body mass index by sex and age. Smoothed BMI-for-age growth curves were presented for both sexes and compared with reference data from other cities of China and WHO. Results BMI centiles increased with age but with different patterns in both boys and girls. The centile curves from the 3rd to the 50th had a slight increase, while a sharp increase was seen from 11 to 17 years in boys and from 6 to 14 years in girls in the higher centiles. In comparison with other cities of China, the values for the 50th percentile are higher than those reported for children from China 2009, Shanghai, Changsha and China 2010 in both sexes. In comparison with WHO growth references, Chinese girls and boys had higher values in all percentiles, whereas curves of girls look roughly the same. The medians for BMI in Shanxi increase linearly from 6 to 17 years in boys. Conclusions The BMI percentiles of children aged 6-17 years in Shanxi differed significantly from the growth reference curves of other cities of China and WHO. Recommending the provision of BMI reference curves for local children and adolescents to assess their growth and development and monitor their nutritional status. Early detection of overweight and obesity in children provides a scientific basis for the prevention and control of overweight and obesity in children.